Políticas públicas da educação profissional no Brasil e na Argentina: análises, desafios e perspectivas - Pinto, Maikol Nascimento (2024)
This thesis aims to analyze the definitions of the technical and professional education policy agendas in Brazil and Argentina in three stages. The first stage presents a critical analysis of the history of professional education in Brazil and Argentina so that it is possible to link and situate the debate on the agendas of this educational modality in both countries. The second stage presents the themes of the public policy agendas in education from the cultural and, above all, professional perspectives that were selected to be analyzed later. The third stage, therefore, analyzes the latest public policy agendas that began to regulate the modality of professional education in Brazil and Argentina through the Public Policy Cycle: in Brazil, by Law No. 11,741 of 2008, approved by the Lula government, which changed the provisions of the Law of Guidelines and Bases of National Education – Law No. 9,394, of December 20, 1996; and in Argentina, by Law No. 26,058/2005, the Ley de Educación Técnico Profesional, approved by the Kirchner Government, put into effect in 2006. Having noticed a gap in knowledge in terms of analysis of this debate and of public policy agendas in professional education, the objectives of this thesis are to investigate and comparatively analyze the public policies of professional education in Brazil and Argentina, enacted in 2008 and 2005, respectively, which brought with them the latest substantial changes in this teaching modality, in order to verify similarities and identify the political and educational challenges and perspectives of both countries. The methodology, therefore, to prepare the comparative analysis of the laws in this thesis is inspired by the Public Policy Cycle because it allows us to see public policy as a deliberative cycle and related to a dynamic learning process. The results of the analysis indicate that, although there are significant differences in the specificities of each country's policies, there are also a number of similarities that suggest common challenges, such as the need for constant updating of educational guidelines to keep up with changes in the labor market and the importance of policies that encourage integration between education and the productive sector, without compromising the autonomy of educational institutions. Finally, the final considerations are presented by way of conclusion